Application of benthic foraminifera to determine ecological status of Panvel Creek and adjoining River Estuaries - Kale Purushottam G (International Journal of Life Sciences, 2017)
Foraminifera, the amoeboid protists, occupy a unique place in the coastal marine ecosystems. These single celled, organisms exist as benthic, planktonic and rarely as terrestrial forms. Their ooze persists in the sediments over prolonged periods. The study of fossil foraminifera is an integral part of paleoceonography, paleoclimology, biostratigraphy. The analysis of foraminifera from sediments and/earth’s crusts is routinely done for oil prospecting. The use of foraminifera as bioindicators of coastal environment has also become common. The comprehensive ecological status was carried out over three years from 2008 to 2010 as a part of EIA project for the proposed site of the International Airport. The study was continued over the subsequent years till 2015. Only a part of the data has been used for this report. The sediment samples collected from 14 stations across Panvel Creek, Gadhi River estuary and Ulwe River estuary were analyzed for physic-chemical parameters and for qualitative as well as quantitative analysis of macrobenthic fauna. Of the modern (living) forams, those belonging to the family Hauerinidae (6 species) and family Rotaliidae were predominant. It was also noticed that the density of foraminifera was maximum in premonsoon, moderate in monsoon and minimum in post-monsoon season. Moreover, the anthropogenic activities have been taking toll on them and the diversity as well as density was found decrease over last 8 years. The construction of the proposed International airport has not started yet and in coming few years as the development intensifies the ecosystem is bound to degrade further. The diversity and density of foraminirerans can be used as bioindicators in following the degradation of the creek ecosystem and the success of the mitigations efforts, if any, undertaken against this degradation.